Particular Manners of Circulation of Classic Chinese Poetry in Thailand - จิรภาส, จรัสศรี (Academic and Research Journal of Liberal Arts (Online), 2019)
This article is a further study of the author’s research of Translations of Classic Chinese Poetry into Thai during Rattanakosin Period published in 2012. This article aims to explain the particular manners of circulation of Classic Chinese Poetry in Thai language from three aspects, namely, 1) scopes and forms of the publishing media; 2) status and qualifications of the translators; and 3) motivative forces of the circulation. This study and analysis was based on Comparative Liturature and literary dissemination methodologies.From the data processed, we can see clearly the circulation of ancient Chinese's verses in Thailand varies in terms of scope and type, and the status of translator of each published item also varies from each other. Furthermore, there are driving forces from "distinctive" individuals and organizations behind many publications that lead to the continuous circulation of ancient Chinese verses in Thailand up to the present.